The Impact of Nutrition Education Using the "My Plate Model with Local Food Nutrition Cards" Mikuzikal Tool on Maternal Knowledge for Stunting Prevention - Muntaha, Yasirul; Hikmah, Nur; Nurliah, Nurliah (Ahmar Metastasis Health Journal, 2024)
Stunting is a serious health issue in Indonesia, with a national prevalence of 27.7% in 2022. West Sulawesi ranks as the second-highest province with a prevalence rate of 35%, while in Mamuju Regency, the prevalence reaches 27.45%. Nutritional education is one of the strategies to improve mothers' knowledge in preventing stunting. This study aims to analyze the effect of nutritional education using the MIKUZIKAL tool ("My Plate Model with Local Food Nutrition Cards") on the knowledge of mothers with children aged 2-5 years in the working area of Puskesmas Bambu, Mamuju Regency. This study employs a quasi-experimental design with a one-group pretest-posttest approach. A total of 54 mothers with young children were selected as research subjects using the total sampling method. Data were collected through questionnaires and analyzed using the Wilcoxon sign rank test. The results show that 35 respondents (64.8%) experienced an increase in post-test scores, 13 respondents (24.1%) experienced a decrease, and 7 respondents (11.1%) had unchanged scores. Statistical analysis revealed a significant difference before and after the intervention (p = 0.001).  In conclusion, nutritional education using MIKUZIKAL positively influences the improvement of mothers' knowledge in preventing stunting. Therefore, this method can be recommended as an educational strategy in healthcare facilities to address stunting issues.